Editorial - Jörg Tremmel; Marisa dos Reis; Joseph Burke; Raphaelle Schwarzberg (†) (Intergenerational Justice Review)
Future generations lack representation in current day politics. Modern representative democracies are largely oriented to the short term. Moreover, our adjunct legal frameworks are ill-equipped to protect those who are disregarded by today’s electorate. This has emerged historically as many European consitutions were originally conceived to protect those in the here-and-now. As such, it is imperative that we reflect on the law and its relation to future people. This poses particular difficulties at both a legal and an institutional level. If law is understood as person-affecting, that is: specifying rights of particular people, it inevitably neglects the interests of the unborn. At the institutional level, our current bodies and decision-making processes already have inherent tendencies towards the recognition and protection of future people, for instance the European Convention on Human Rights has been interpreted progressively. Nevertheless, it requires innovative thinking to imagine alternative provisions that can complement today’s legal architecture but revolutionise our restricted thinking on this topic. This issue of IGJR attempts to draw attention to these important legal matters with the work of a wide range of professionals and academics who are working to address these questions.